Dehydrogenase enzyme cytochemistry of unfixed leucocytes. Issue 6 (September 1970) - Stuart, John; Simpson, Jennifer S.
Abstract : An inert, synthetic, sucrose polymer (Ficoll) has been found to have a protective effect on leucocytes during incubation for cytochemical reactions at 37°C. This permits enzyme cytochemistry to be performed on unfixed bone marrow and peripheral blood smears, and on leucocytes cultured in vitro, thus avoiding enzyme inhibition by the use of a fixative. The technique is suitable for the demonstration of both cytoplasmic and intramitochondrial dehydrogenase enzyme activity.